2007
DOI: 10.1002/cm.20189
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated mortality from hydrocephalus and pneumonia in mice with a combined deficiency of SPAG6 and SPAG16L reveals a functional interrelationship between the two central apparatus proteins

Abstract: SPAG6 and SPAG16L are proteins localized to the "9+2" axoneme central apparatus. Both are essential for sperm motility and male fertility. These two proteins are also expressed in other tissues containing ciliated cells, such as brain and lung. To study the effects of combined deficiency of these two proteins, a double mutant mouse model was created. The double mutant mice displayed a more profound phenotype of growth retardation and hydrocephalus compared to mice nullizygous for SPAG6 and SPAG16L alone. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 66 publications
3
57
1
Order By: Relevance
“…When Western blotting was performed with fresh samples, the SPAG16L level in heterozygous sperm was half that in the sperm of wild-type littermates, although there were no differences in SPAG6 and SPAG17 protein expression, which is consistent with our previous observations [28,34]. However, when the samples were frozen/boiled four times and Western blotting was repeated, as seen for the human samples, SPAG16L, SPAG6, and the 28-kDa fragment of the SPAG17 protein were markedly reduced in the heterozygous mutant sperm but not in the sperm of wild-type mice.…”
Section: Discussionsupporting
confidence: 89%
“…When Western blotting was performed with fresh samples, the SPAG16L level in heterozygous sperm was half that in the sperm of wild-type littermates, although there were no differences in SPAG6 and SPAG17 protein expression, which is consistent with our previous observations [28,34]. However, when the samples were frozen/boiled four times and Western blotting was repeated, as seen for the human samples, SPAG16L, SPAG6, and the 28-kDa fragment of the SPAG17 protein were markedly reduced in the heterozygous mutant sperm but not in the sperm of wild-type mice.…”
Section: Discussionsupporting
confidence: 89%
“…Some genes were found exclusively involved in XY gonad development. For 1-year-old juveniles, only four sex-related genes uniquely expressed in XY gonads were identified: 1) rhophilin-associated protein 1 (ROPN1), an important reproduction-related gene, has been identified as a spermatogenic cell-specific protein and may be involved in sperm maturation, motility, capacitation, hyperactivation, and acrosome reaction (7,13,34); 2) sperm-associated antigen 6 (SPAG6), which has been shown to be a critical protein in either the assembly or structural integrity of the sperm tail axoneme (28,68,69); 3) spermassociated antigen 16 (SPAG16), which plays an essential roles for spermatogenesis, germ cell viability, and the integrity of the axoneme (67); and 4) fibroblast growth factor-binding protein 2 (FGFBP2); it has been found that high FGFBP2 expression in high-grade gliomas is positively correlated with survival, and it also is more closely correlated with survival than histological grade (11,62) (Table 9).…”
Section: Resultsmentioning
confidence: 99%
“…Sinusitis and otitis media were seen in mouse mutants lacking the Wnt inhibitor Cby1 (MIM# 607757) that were unable to clear bacteria from the sinuses upon intranasal bacterial challenge leading to upper airway inflammation, however additional morphological pulmonary defects were also evident from shortly after birth [Love et al, 2010]. Strikingly, lower airway disease, including pneumonia, was reported for Spag6 (MIM# 605730), Spag16 (MIM# 6121736) double mutants, however mortality is very high with 100% lethality by 5 weeks of age, making it far more severe than human PCD [Zhang et al, 2007]. It is tempting to speculate that it is the presence of chronic infection in man, taking place over a period of years rather than months, which is responsible for bronchiectasis and other lung pathology rather than a direct link to dyskinesia.…”
Section: Discussionmentioning
confidence: 99%